CHALLENGES IN THE PREVENTION AND CONTROL OF RABIES DISEASE - Henny, Henny; Hasyim, Hamzah; Syahputra, Ibrahim Syahputra; Rahmatilah, Imat; Arifin, Jafar Arifin; Aini, Kurnia; Zuliana, Linda; Pitrianti, Lisa (Jurnal Kesehatan - STIKes Prima Nusantara, 2021)
Background: The death rate due to Rabies in Indonesia is still quite high at 100-156 deaths per year, with a Case Fatality Rate of almost 100 percent. This illustrates that rabies is still a threat to public health. Statistically 98% of rabies is transmitted through dog bites, and 2% of the disease is transmitted by cats and monkeys.Purpose: make a literature review on rabiesMethod: using the literature review method by looking for articles related to the rabies theme on Pubmed, so that 30 articles were obtained according to the theme and extractedResult: Recognizing the disease's intricacy and manner of transmission might help to inform prevention and control approaches. The development and implementation of effective rabies elimination programs should involve veterinarians, public health professionals, physicians, ecologists, and vaccine manufacturers. Synchronization of operations through a multidisciplinary approach increases the likelihood of overcoming technical and infrastructural impediments to regional forces that drive disease management under the One Health concept.Keyword: Rabies; Disease: Rabies Disease: Literature Review